A high conductivity aluminum alloy core reinforced insulated aerial cable

CN123017606APending Publication Date: 2026-10-30ZHONGDONG CABLE MFR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611483470.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本申请的目的是提供一种高导电率铝合金芯加强型绝缘架空电缆,旨在改善现有技术中架空电缆在长跨距和复杂气候环境下运行过程中存在抗拉强度衰减、易发生机械蠕变以及绝缘层由于内外结构应力分布不均导致的局部老化龟裂缺陷的问题

Benefits of technology

[0033]1.本申请通过将特定成分配比的高导电率铝合金芯与具有轴向预张应力的不锈钢丝加强层结合,改变了传统架空电缆的受力机制,铝合金基体中生成的纳米析出相在保证导电率的同时提升了材料基础强度,同时利用异质金属冷却阶段热膨胀系数差在不锈钢丝内固化的预张应力,使得电缆在承受外部载荷时能够优先消耗预设的应力裕度,使缆芯在长跨距架设中具备更稳定的抗拉伸能力,降低了机械蠕变发生的概率;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017606A_ABST
    Figure CN123017606A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of electric wire and cable, and discloses a high-conductivity aluminum alloy core reinforced insulated overhead cable, which comprises a high-conductivity aluminum alloy core, a stainless steel wire reinforcing layer and a cross-linked polyethylene insulation layer. The aluminum alloy core contains Fe, Si, Mg and Zr elements in a specific proportion, and the nanometer precipitated phase in the matrix takes into account high conductivity and mechanical strength; the stainless steel wire reinforcing layer is spirally twisted on the outer periphery of the aluminum alloy core, the inside of the reinforcing layer is solidified with axial pre-tension stress and forms a ring-shaped fastening structure, and the mechanical creep of the wire core is greatly inhibited; the insulation layer is coated on the outside of the reinforcing layer and is made of polyethylene resin, aluminum oxide and silane cross-linking agent, etc., and the cross-linking degree difference between the outermost side and the innermost side in the thickness direction of the insulation layer is less than or equal to 1.53%, so that the structural stress difference in the material is eliminated. The application improves the tensile stability of the overhead cable in a long-span environment and prevents local aging and cracking of the insulation layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of wire and cable technology, specifically to a high-conductivity aluminum alloy core reinforced insulated overhead cable. Background Technology

[0002] As power grid construction extends over long spans and across complex terrains, higher demands are placed on the comprehensive mechanical performance and environmental adaptability of overhead cables. Traditional aluminum alloy overhead cables, when subjected to long-term loads such as their own weight and external loads like wind and ice, are prone to grain boundary slip in the metal matrix. This leads to a decrease in the tensile strength of the material and mechanical creep, which increases cable sag and reduces the operational safety of the line. To improve the cable's load-bearing capacity, existing technologies typically employ methods such as increasing the steel core or significantly adjusting the alloy composition, but this results in a loss of overall cable conductivity. Furthermore, conventional metal load-bearing structures lack internal stress buffering mechanisms when facing alternating external stresses, limiting their ability to resist long-term fatigue damage.

[0003] Regarding insulation structure, the outer insulation layer of overhead cables is exposed to the outdoor environment for extended periods, facing risks of thermo-oxidative aging and mechanical damage. Currently, the cross-linked polyethylene insulation layer of cables often employs a rapid water-cooling process after extrusion molding. This process rapidly solidifies the surface layer of the insulation material, while internal heat dissipation is slower. Differences in cooling rates lead to inconsistent cross-linking processes along the thickness of the insulation layer, resulting in a significant gradient deviation in the degree of cross-linking between the inner and outer sides. This uneven cross-linking structure creates residual stress within the material. When the cable experiences repeated changes in ambient temperature during actual service, this internal stress concentration can easily lead to localized micro-cracks or even large-area cracking in the insulation layer.

[0004] Furthermore, in low-temperature and high-humidity climates, supercooled water droplets easily adhere to and freeze on the surface of overhead cables. Accumulated ice on the cable surface increases the external mechanical load, further exacerbating the tensile deformation and creep risks to the internal metal core, and also damaging the physical integrity of the insulation layer. Therefore, comprehensive improvements are needed in conductor structure and insulation material molding processes. Summary of the Invention

[0005] The purpose of this application is to provide a high-conductivity aluminum alloy core reinforced insulated overhead cable, which aims to improve the problems of tensile strength decay, easy mechanical creep, and local aging and cracking defects caused by uneven stress distribution of internal and external structures in the insulation layer of existing overhead cables during operation in long spans and complex climatic environments.

[0006] To achieve the above objectives, the present invention provides a high-conductivity aluminum alloy core reinforced insulated overhead cable, employing the following technical solution:

[0007] A high conductivity aluminum alloy core reinforced insulated overhead cable includes a high conductivity aluminum alloy core, a stainless steel wire reinforcing layer wound around the outer periphery of the aluminum alloy core, and a cross-linked polyethylene insulation layer covering the outer surface of the stainless steel wire reinforcing layer.

[0008] The high conductivity aluminum alloy core contains the following components by weight percentage: Fe 0.12-0.15wt%, Si 0.05-0.07wt%, Mg 0.02-0.03wt%, Zr 0.008-0.010wt%, with the balance being Al and unavoidable impurities;

[0009] The stainless steel wire reinforcing layer is a prestressed network layer made of 316L stainless steel wire spirally twisted together. The stainless steel wire reinforcing layer has axial prestress cured inside and is tightly wrapped around the surface of the aluminum alloy core.

[0010] The cross-linked polyethylene insulation layer is made from raw materials comprising the following parts by weight: 100 parts polyethylene resin; 0.4 to 0.45 parts alumina; 0.1 to 0.15 parts hindered phenolic antioxidant; and 1.5 to 2.5 parts silane cross-linking agent.

[0011] The difference between the outermost and innermost crosslinking degrees of the crosslinked polyethylene insulation layer in the thickness direction is ≤1.53%, wherein the outermost crosslinking degree is the crosslinking degree within 0.5 mm from the outer surface of the insulation layer, and the innermost crosslinking degree is the crosslinking degree of the insulation layer close to the surface of the stainless steel wire reinforcing layer.

[0012] By adopting the above technical solution, this invention establishes an effective synergistic mechanism between the microstructure and macroscopic mechanical structure of the material. Specifically, the introduction of trace zirconium elements into the matrix alloy promotes the precipitation of intermetallic compounds. These precipitated phases can effectively pin grain boundaries and hinder dislocation movement, thus balancing conductivity and mechanical strength without significantly increasing the free electron scattering cross-section. Furthermore, by strictly controlling the solid solution content of impurities or trace elements such as iron, silicon, and magnesium, efficient power transmission is further guaranteed. Regarding mechanical load-bearing capacity, unlike the passive load-bearing mode of traditional cores that rely solely on the yield strength of the material itself, the prestressed network layer constructed in this invention applies circumferential tightening pressure to the surface of the aluminum alloy core and pre-solidifies axial prestress within the stainless steel wire. When the cable is subjected to external wind or ice loads under complex climatic conditions, this structure can preferentially consume the pre-stored stress margin, thereby significantly delaying the time it takes for the cable core to enter the plastic deformation stage and fundamentally suppressing creep. For the external insulation structure, the alumina particles in the formulation optimize the polymer's thermal conduction path and, in conjunction with the hindered phenolic antioxidants, capture free radicals, thus interrupting the thermo-oxidative aging chain reaction. More importantly, the difference in crosslinking degree between the inner and outer sides of the insulation layer is controlled to an extremely low level, eliminating structural stress differences caused by uneven crosslinking within the material and preventing localized cracking that may occur when facing drastic temperature changes during long-term service.

[0013] The formation of the three-dimensional network cross-linked structure within the insulating matrix primarily depends on the chemical bonding between silane molecules and polyethylene segments. During the heated state in the early stages of extrusion, the initiator induces the polyethylene macromolecular chains to generate free radicals, prompting the vinyl groups contained in the silane cross-linking agent to undergo an addition reaction, grafting siloxane side groups onto the polyethylene backbone. Subsequently, with the combined participation of environmental moisture and a catalyst, these segments with siloxane side groups undergo hydrolysis and transform into silanol groups. Adjacent silanol groups further spontaneously condense and dehydrate, ultimately forming stable Si-O-Si siloxane bonds, firmly weaving the originally isolated linear macromolecules into a spatial cross-linked network.

[0014] Preferably, the high conductivity aluminum alloy core has the following weight percentage composition: Fe 0.12wt%, Si 0.05wt%, Mg 0.02wt%, Zr 0.0095wt%; and the aluminum alloy core matrix has Al3Zr nano-precipitates with a size of 10nm dispersedly distributed inside.

[0015] By adopting the above technical solution, the Al3Zr nano-precipitates spontaneously formed by the set ratio system are confined to a size range of 10 nm. The precipitates at this microscale can not only give full play to the dispersion strengthening effect to improve the tensile strength of the matrix, but also avoid the contradiction between strength and electrical conductivity in traditional alloying processes because their geometric size has not yet reached the critical threshold for triggering significant electron scattering.

[0016] Preferably, the axial prestress in the stainless steel wire reinforcing layer is 346.8 to 400 MPa, and the grain size inside the 316L stainless steel wire is ≤2.5 μm.

[0017] By adopting the above technical solution, the axial prestress is stabilized within a specific range, giving the cable core the stress buffer required to cope with the self-weight and additional loads of long-span installations; combined with 316L stainless steel wire with grain size refined to 2.5μm and below, the overall fatigue limit is improved from the material body level by utilizing the fine grain strengthening effect.

[0018] Preferably, in the cross-linked polyethylene insulation layer raw material, the alumina has an average particle size of 20-40 nm and a specific surface area of ​​85-110 m² / g; the hindered phenolic antioxidant is antioxidant 1010.

[0019] By adopting the above technical solution, alumina with a specific surface area and particle size morphology can achieve an extremely high interfacial contact with the polyethylene matrix. The presence of this dense bonding layer increases the barrier to space charge injection and migration. At the same time, the hindered phenolic antioxidant with a specific structure can sustainably and stably provide phenolic hydroxyl hydrogen atoms by means of its steric hindrance characteristics, so as to neutralize free radicals derived from polymer chain breakage.

[0020] Preferably, two copper-plated constantan wires are embedded parallel to each other along the axial direction inside the cross-linked polyethylene insulation layer. The outer surface of the copper-plated constantan wires is covered with a polyimide film with a thickness of 0.03 mm. The copper-plated constantan wires are spaced 2.5 mm apart, have a diameter of 0.18 mm, and have a temperature coefficient of resistance of ±5×10-6 / ℃.

[0021] By adopting the above technical solution, the pre-embedded copper-plated constantan wire, with its weak resistance temperature sensitivity, serves as a physical probe for monitoring the actual strain and thermal state inside the cable. The polyimide film covering its surface provides necessary electrical isolation to maintain signal purity, while the copper plating treatment on the surface improves the problem of easy peeling between the metal wire and the cross-linked polyethylene matrix from the perspective of interfacial affinity, ensuring the synchronicity of deformation transmission.

[0022] Preferably, the outer surface of the cross-linked polyethylene insulation layer is further coated with an anti-icing functional layer, the thickness of which is 0.15-0.18 mm, and is formed by drying a mixed coating liquid containing a fluorinated acrylate copolymer and a hydrophobic silica aerogel.

[0023] By adopting the above technical solution, the anti-icing functional layer attached to the outermost side of the insulation layer acts as a physical barrier, blocking the direct adhesion path between supercooled water droplets in the atmosphere and the insulation material, thereby macroscopically slowing down the process of ice crystal nucleation and crust formation.

[0024] Preferably, the mass ratio of the fluorinated acrylate copolymer to the hydrophobic silica aerogel in the mixed coating liquid is 7:3; the fluorinated acrylate copolymer is a polymer compound containing trifluoroethyl side groups and having a glass transition temperature of -15°C; the hydrophobic silica aerogel has a porosity ≥92% and a particle size of 50-100 nm.

[0025] By employing the above technical solution, the anti-icing capability of this functional layer stems from the physicochemical synergy between the polymer's low surface energy and its microscopically rough structure. The trifluoroethyl side groups carried by the fluorinated acrylate copolymer possess extremely low surface free energy, while the highly porous hydrophobic silica aerogel mixed within it constructs a micro-nano-scale undulating morphology on the coating surface. This superhydrophobic state forces contacting water droplets to maintain a large contact angle and a very small roll-off angle, allowing them to naturally slide off the cable surface by gravity or a gentle breeze before completely freezing.

[0026] Preferably, the stainless steel wire reinforcing layer is formed by winding 316L stainless steel wire with a diameter of 0.8 mm in a left-hand spiral twisting manner, with a pitch diameter ratio of 12 to 14 and a twisting tension of 120 to 150 N.

[0027] By adopting the above technical solution, the standardized left-hand spiral stranding method, combined with a specific pitch ratio and tension control, ensures that the geometric deformation of each stainless steel wire is highly consistent in the initial stage of mesh formation. This not only avoids localized stress concentration but also lays a mechanical foundation for the uniform excitation of prestress in subsequent heat treatment processes.

[0028] Preferably, the axial prestress in the stainless steel wire reinforcing layer is formed by a composite segment of the stainless steel wire and the aluminum alloy core containing initial stranding tension, which is subjected to low-temperature aging treatment at 180-190°C for 2 hours and then cooled to room temperature for curing.

[0029] By employing the above technical solution, the final forming of complex prestressed wires cleverly utilizes the differences in thermodynamic properties between heterogeneous materials. After undergoing isothermal aging treatment to eliminate disordered residual stresses derived from stranding, the composite wire segment enters the cooling stage. At this point, due to the significantly larger coefficient of thermal expansion of the aluminum alloy core, its volume shrinkage caused by cooling far exceeds that of the outer stainless steel wire. Under the boundary conditions constrained at both ends, the intense shrinkage of the aluminum alloy core conversely restricts the free retraction space of the stainless steel wire, forcing the corresponding axial tensile stress to be generated inside the stainless steel wire. This thermally induced stress, superimposed with the previous mechanical stranding tension, is ultimately solidified in the network layer.

[0030] Preferably, the crosslinking degree distribution of the inner and outer sides of the crosslinked polyethylene insulation layer is formed by a segmented gradient cooling process after the raw material is extruded and coated at 195-200°C, and then subjected to water cooling at a first stage of 50°C and a cooling length of 1.2m, and air cooling at a second stage of 28°C and a cooling length of 0.8m.

[0031] By adopting the above technical solution, the uniform distribution of crosslinking degree benefits from the segmented gradient cooling strategy implemented after extrusion, which overcomes the technical disadvantages of traditional single rapid cooling processes that easily lead to a sudden drop in melt surface temperature and distortion of internal and external temperature differences. The first stage of water cooling with specific water temperature and cooling length promotes the initial shaping of the surface polymer melt at a relatively gentle rate, suppressing the excessive expansion of the cross-sectional temperature gradient; the subsequent air cooling stage further smoothly removes the residual heat from the structure. This relatively gentle heat dissipation process provides ample time for the conformational relaxation of the macromolecular chain segments inside the insulating matrix and the hydrolysis and condensation of silane molecules, enabling the crosslinking network of the entire radial cross-section to develop synchronously, reducing the difference in crosslinking degree between the inner and outer sides from the source of the process.

[0032] In summary, this application includes at least one of the following beneficial technical effects:

[0033] 1. This application changes the stress mechanism of traditional overhead cables by combining a high conductivity aluminum alloy core with a stainless steel wire reinforcement layer with axial prestress in a specific composition ratio. The nano-precipitates generated in the aluminum alloy matrix improve the basic strength of the material while ensuring conductivity. At the same time, the prestress solidified in the stainless steel wire by the difference in thermal expansion coefficients during the cooling stage of dissimilar metals allows the cable to preferentially consume the preset stress margin when subjected to external loads, so that the cable core has more stable tensile strength in long-span installation and reduces the probability of mechanical creep.

[0034] 2. This application optimizes the material system and molding process of the insulation layer. By adding alumina and hindered phenolic antioxidants, thermo-oxidative aging is inhibited, and a segmented gradient cooling process with specific parameters is used for extrusion shaping. Gradient cooling slows down the heat dissipation rate during the melt cooling stage, providing time for the synchronous hydrolysis and polycondensation reaction of polymer chain segments on the radial cross section. The difference in crosslinking degree between the outermost and innermost sides of the insulation layer is controlled below 1.53%, eliminating the structural stress accumulation caused by uneven crosslinking degree distribution inside the insulation material, and preventing local cracking defects in the cable when the service temperature changes.

[0035] 3. This application coats the outside of the cross-linked polyethylene insulation layer with an anti-icing functional layer composed of fluorinated acrylate copolymer and hydrophobic silica aerogel, which improves the operational reliability of the cable in complex climatic environments. The low surface free energy of the fluorinated polymer and the high porosity and rough structure provided by the silica aerogel work together to create a superhydrophobic physical state on the cable surface, increasing the surface tension of water droplets in contact with the cable. This causes the supercooled water droplets to slide off naturally by their own weight before they freeze completely, thus delaying the formation of ice on the line. Attached Figure Description

[0036] Figure 1 This is a comparison diagram of the time and creep deformation behavior of the wire core under constant tension loading at 80℃ in this application;

[0037] Figure 2 This is a graph showing the relationship between the macroscopic surface wetting characteristics, ice adhesion strength, and de-icing wind speed distribution of this application. Detailed Implementation

[0038] The following is in conjunction with the appendix Figure 1 - Appendix Figure 2 This application will be described in further detail below.

[0039] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0040] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.

[0041] The zirconium content in the aluminum-zirconium master alloy is 5% by mass. The alumina (CAS No. 1344-28-1) has an average particle size of 20 to 40 nm and a specific surface area of ​​85 to 110 m² / g. The hindered phenolic antioxidant is antioxidant 1010 (CAS No. 6683-19-8). The fluorinated acrylate copolymer is a polymer containing trifluoroethyl side groups in its molecular chain and has a glass transition temperature of -15 °C. The hydrophobic silica aerogel (CAS No. 112945-52-5) has a porosity ≥92% and a particle size of 50 to 100 nm. The copper-plated constantan wire has a diameter of 0.18 mm and a temperature coefficient of resistance of ±5 × 10⁻⁶ / °C.

[0042] Examples 1-3:

[0043] Example 1:

[0044] This embodiment provides a high conductivity aluminum alloy core reinforced insulated overhead cable, including the following steps:

[0045] S1. Pure aluminum ingots are heated and melted. 0.15wt% Fe, 0.07wt% Si, 0.03wt% Mg and aluminum-zirconium master alloy are added according to the weight percentage, so that the Zr content is 0.010wt%, with the balance being Al and unavoidable impurities. The refining operation is carried out at a controlled melting temperature of 720℃. After refining, the ingot is held at the temperature for 45 minutes. Then, it is continuously cast, rolled and drawn to produce a high conductivity aluminum alloy core with a diameter of 8.5mm. Al3Zr nano-precipitates with a size of 12nm are formed inside the matrix.

[0046] S2. A 0.8mm diameter 316L stainless steel wire is wound around the outer circumference of the high-conductivity aluminum alloy core using a left-hand spiral twisting method, with a pitch ratio controlled at 13 and a twisting tension controlled at 140N. The composite core is then placed in a heat treatment furnace for low-temperature aging treatment at 180℃ for 2 hours, followed by cooling to room temperature. After treatment, the prestress value within the stainless steel wire is stabilized at 385MPa, and the stainless steel wire grain size is 2.5μm, forming a stainless steel wire reinforcing layer.

[0047] S3. Polyethylene resin, 0.4 phr of alumina (with an average particle size of 30 nm and a specific surface area of ​​95 m² / g) per 100 parts of resin, and 0.1 phr of hindered phenolic antioxidant were blended, and 2.0 phr of silane crosslinking agent was added. The mixture was extruded at 195°C and coated onto the outer surface of the stainless steel wire reinforcing layer, with the overall extrusion thickness controlled at 3.4 mm. The extruded cable then entered a cooling system for a segmented cooling process: the first segment used water cooling at 50°C for a length of 1.2 m, and the second segment used air cooling at 28°C for a length of 0.8 m. Subsequently, a silane grafting wet crosslinking reaction was completed to form a crosslinked polyethylene insulation layer. Sampling and testing showed that the difference between the outermost crosslinking degree within 0.5 mm of the outer surface and the innermost crosslinking degree close to the surface of the stainless steel wire reinforcing layer was 1.53%.

[0048] In this embodiment, the axial prestress cured within the stainless steel wire reinforcing layer and the small difference in cross-linking degree between the inner and outer sides in the thickness direction of the insulation layer cannot be accurately defined by conventional structural parameters. Their physical state needs to be solidified and shaped by the low-temperature aging treatment at the set temperature and the segmented gradient cooling process mentioned above.

[0049] Example 2:

[0050] This embodiment provides a high conductivity aluminum alloy core reinforced insulated overhead cable, including the following steps:

[0051] S1. Same as Example 1, except that the Zr content is adjusted to 0.008wt% and the melting temperature is controlled at 720℃. The rest of the process is the same as in Example 1 to produce a high conductivity aluminum alloy core, in which Al3Zr nano-precipitates with a size of 8nm are formed inside the matrix.

[0052] S2. 316L stainless steel wire with a diameter of 0.8mm is wound in a left-hand spiral twisting method with a pitch diameter ratio controlled at 12 and a twisting tension controlled at 120N. After low-temperature aging treatment at 180℃ and cooling shrinkage, the prestress value in the stainless steel wire is stabilized at 346.8MPa and the grain size of the stainless steel wire is 2.3μm.

[0053] S3. Extruded cross-linked polyethylene insulation layer (containing the same amount of silane cross-linking agent) as in Example 1. The degree of cross-linking was measured using the same standard, and the difference was 1.24%.

[0054] S4. A fluorinated acrylate copolymer (the copolymer contains trifluoroethyl side groups in its molecular chain and its glass transition temperature Tg is -15℃) and a hydrophobic silica aerogel (its porosity is ≥92% and its particle size is 50-100nm) are mixed and dispersed at a mass ratio of 7:3 to prepare a coating liquid. The coating liquid is applied to the outer surface of the cross-linked polyethylene insulation layer and dried to form an anti-icing functional layer with a thickness of 0.15mm.

[0055] Example 3:

[0056] This embodiment provides a high conductivity aluminum alloy core reinforced insulated overhead cable, including the following steps:

[0057] S1. Heat and melt pure aluminum ingots, and add 0.12wt% Fe, 0.05wt% Si, 0.02wt% Mg and aluminum-zirconium master alloy (added in the form of Al-5Zr) according to the weight percentage, so that the Zr content is 0.0095wt%, with the balance being Al and impurities. Control the melting temperature at 730℃ for refining. After refining, let it stand for 50 minutes to make a high conductivity aluminum alloy core with a diameter of 8.5mm. At this time, Al3Zr nano-precipitates with a size of 10nm are formed inside the matrix.

[0058] S2. 0.8mm stainless steel wire is wound with a pitch ratio controlled at 14 and a stranding tension controlled at 150N. After low-temperature aging treatment at 190℃ for 2 hours and cooling shrinkage, the prestress value is stabilized at 400MPa. The grain size of the treated stainless steel wire is 2.0μm.

[0059] S3. Polyethylene resin, 0.45 phr alumina (average particle size 20-40 nm, specific surface area 85-110 m² / g), and 0.15 phr hindered phenolic antioxidant (specifically antioxidant 1010) are blended and 2.0 phr silane crosslinking agent is added. The mixture is extruded and coated at 200°C. Simultaneously, during extrusion, two copper-plated constantan wires (0.18 mm in diameter, temperature coefficient of resistance α ±5 × 10⁻⁶ / °C) with an outer polyimide film thickness of 0.03 mm are embedded parallel to the cable axis into the extruded layer, spaced 2.5 mm apart. Segmented cooling is then performed: the first segment is water-cooled at 50°C (1.2 m), and the second segment is air-cooled at 28°C (0.8 m), forming a crosslinked polyethylene insulation layer. Sampling and testing according to the same standard showed a crosslinking degree difference of 0.84%.

[0060] S4. Coating with a fluorinated acrylate copolymer and hydrophobic silica aerogel (mass ratio 7:3) to form an anti-icing functional layer with a thickness of 0.18 mm.

[0061] Comparative Examples 1-5:

[0062] Comparative Example 1:

[0063] Compared with Example 2, the difference is that no aluminum-zirconium master alloy was added in step S1, that is, the Zr content in the aluminum alloy core is 0, and the rest are the same.

[0064] Comparative Example 2:

[0065] Compared with Example 2, the difference is that no microalloying elements were added in step S1 (pure aluminum was used instead of the high conductivity aluminum alloy core), and step S2 was cancelled. That is, the pure aluminum core was not wrapped with 316L stainless steel wire and was not subjected to low temperature aging treatment. It directly entered step S3 for insulation layer extrusion. All other aspects are the same.

[0066] Comparative Example 3:

[0067] Compared with Example 2, the difference is that in step S2, the stainless steel wire is wound in a conventional tension-free loose twisting method, no circumferential prestress is established in the stainless steel wire, and the composite core is not subjected to low-temperature aging treatment at 180°C after twisting. All other aspects are the same.

[0068] Comparative Example 4:

[0069] Compared with Example 2, the difference is that aluminum oxide was not added when preparing the insulation layer in step S3, and the extruded and coated cable was rapidly cooled in one stage with conventional 20°C cooling water instead of a segmented gradient cooling process. All other aspects are the same.

[0070] Comparative Example 5:

[0071] Compared with Example 2, the difference is that in step S4, the coating liquid is only dispersed from fluorinated acrylate copolymer and no hydrophobic silica aerogel is added, while the rest are the same.

[0072] Test Example 1-3:

[0073] Test Example 1: Dimensional Stability and Combined Mechanical and Electrical Performance Testing under Thermo-Mechanical Coupling

[0074] Experimental description:

[0075] The metal composite wire cores (without stripped or extruded insulation layer) prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were used as experimental objects. The samples were cut into standardized specimens with a length of 15m and fixed at both ends with crimping hardware.

[0076] After sample preparation, X-ray diffraction was used to determine the axial residual lattice strain on the outer surface of the stainless steel, and the measured residual prestress value was calculated according to Hooke's law in elasticity. Simultaneously, electron backscattering diffraction was used to analyze the grain size of the stainless steel wire, and transmission electron microscopy was used to observe the morphology and size of the precipitates inside the aluminum matrix. A high-precision DC double-arm bridge was used to measure the volume resistivity of each sample at a constant temperature of 20℃, and the result was converted to conductivity (%IACS). Subsequently, a horizontal universal tensile testing machine was used at room temperature to perform fracture tests on the samples at a tensile rate of 50 mm / min, the maximum fracture load was recorded, and the equivalent tensile strength was calculated.

[0077] The assembled specimen was placed in a large thermo-mechanical coupling environment chamber, and the chamber temperature was set to a stable 80°C to simulate the conductor heating under heavy load operation of the cable. A constant axial tension equivalent to 30% of its rated breaking force was applied to the specimen using a servo loading system. During the continuous 1000-hour load holding period, the elongation deformation of the line segment was captured in real time using a laser displacement sensor array arranged along the specimen axis. After the experiment, the cumulative creep percentage over 1000 hours was calculated based on the cumulative deformation.

[0078] In addition, to evaluate the fatigue resistance under alternating climates, another set of samples of the same specifications were placed in a high and low temperature alternating environment test chamber and subjected to 1000 thermal cycles (each cycle was set as follows: holding at -40℃ for 1 hour, followed by a rapid switch to +90℃ for 1 hour). After the experiment, the sag rate of the samples after 1000 thermal cycles was calculated using the 15m span catenary equation.

[0079] Table 1: Record of Basic Performance and Thermo-Mechanical Coupling Test Data of Composite Core

[0080] Experimental subjects Measured prestressing value (MPa) Tensile strength (MPa) Electrical conductivity (%IACS) Cumulative creep variation over 1000 hours (%) Sag change rate (%) after 1000 thermal cycles Example 1 385.0 184.6 58.62 0.251 0.408 Example 2 346.8 181.3 58.19 0.279 0.435 Example 3 400.0 189.5 58.91 0.207 0.381 Comparative Example 1 351.2 172.4 59.85 0.652 0.887 Comparative Example 2 / 163.7 61.23 1.834 2.146 Comparative Example 3 24.5 178.6 58.54 0.942 1.153

[0081] Note: / indicates that there is no stainless steel wire reinforcement layer, no prestressed structure, and this indicator test is neither possible nor necessary.

[0082] in conclusion:

[0083] According to the data in Table 1, after introducing aging treatment and thermal shrinkage processes, the stainless steel reinforcing layers of Examples 1 to 3 successfully cured pre-tension stresses ranging from 346.8 to 400 MPa (and EBSD microscopic observation confirmed that the grain size of the treated stainless steel wire was refined and controlled to ≤2.5 μm). This indicates that the mechanism of macroscopic tension control combined with the difference in the coefficient of linear expansion is indeed feasible. A comparison of basic mechanical and electrical parameters revealed an intrinsic conflict between high conductivity and mechanical strength in all-aluminum substrates. Comparative Example 2, which contained no alloying elements or steel wire, retained the highest conductivity of 61.23% IACS, but its tensile strength was only 163.7 MPa. The examples, through the synergistic effect of trace amounts of Zr, Fe, and Si, and the mechanical load-bearing capacity of the stainless steel layer, ensured that the conductivity remained above the industrial requirement threshold of 58% IACS while raising the tensile strength to over 180 MPa, achieving a reasonable comprehensive balance in actual conductor manufacturing selection.

[0084] High-temperature creep testing can reflect the microstructural stability of wires. Combined with... Figure 1The graph showing the comparison of creep deformation behavior of each group of wire cores under constant tension loading at 80℃ shows that the horizontal axis represents the constant tension holding time of the sample in the thermo-mechanical coupling environment chamber, ranging from 0 to 1000h, and the vertical axis represents the percentage of cumulative creep along the axial direction of the cable sample under this condition. In Comparative Example 2, under 80℃ environment and constant external tension, the internal grain boundary slip resistance decreased, which is represented by a thin curve with hollow circular markings in the graph, showing a rapid upward trajectory, resulting in a cumulative creep of 1.834% at the end of the 1000h test. This irreversible plastic elongation converted from stress relaxation is more pronounced in thermal cycling tests. After experiencing 1000 alternating shocks from extreme cold (-40℃) to high heat (+90℃), Comparative Example 2 directly resulted in a sag variation as high as 2.146% in engineering applications. Even with external stainless steel wire winding, as in Comparative Example 3 which uses a conventional loose winding process, and despite a weak residual stress of 24.5 MPa after forming, the lack of sufficient initial prestressing force causes strain mismatch between the inner core and outer layer in the early stages of tension, resulting in a creep rate of 0.942%. The introduction of the prestressed network alters the stress distribution pattern in the early stages of tension. In this example, the pre-tensioned stress stored in the stainless steel layer offsets the initial yielding tendency of the aluminum matrix caused by the external load. More importantly, due to the significant difference in thermal expansion coefficients between the stainless steel wire and the aluminum alloy core (stainless steel 16 × 10⁻⁶ / K, aluminum alloy 23 × 10⁻⁶ / K), during cooling and shaping, and the subsequent thermal expansion and contraction stages in operation, the stainless steel wire applies a tight circumferential compressive stress to the surface of the internal aluminum alloy substrate. This constitutes the core physical mechanism for synergistically suppressing high-temperature creep of the conductor.

[0085] Comparative Example 1, lacking trace amounts of Zr, failed to form dispersed nano-aluminum zirconium precipitates within the matrix. At high temperatures, dislocation movement lost its pinning source, leading to a creep increase to 0.652%. In contrast, Example 3, under the combined effects of approximately 400 MPa pre-tension stress, external circumferential compressive stress, and 0.0095 wt% microalloying (TEM observation confirmed the presence of numerous 10 nm Al3Zr nano-precipitates dispersed within the matrix), showed a clear convergence trend in the later stages of testing, with the creep ultimately settling at 0.207%. This structure, combining dislocation pinning by the Al3Zr precipitates and the combined stress field, reduced the material's deformation under thermal and mechanical conditions, maintaining a sag rate of less than 0.4% for the cable under alternating high and low temperature conditions.

[0086] Test Example 2: Insulation Layer Spatial Homogeneity and Smart Sensing Response Test

[0087] Experimental description:

[0088] The overhead cable samples prepared in Examples 1 to 3 and Comparative Example 4 were used as experimental subjects, and cable segments with a length of 2m were cut. Samples were cut layer by layer radially along the insulation layer, and the outermost sample within 0.5mm from the outer surface and the innermost sample close to the surface of the inner stainless steel reinforcing layer were collected. The gel content of each sample layer was determined using the xylene solvent extraction method to characterize the crosslinking degree distribution of the insulation layer in the thickness direction, and the difference in crosslinking degree between the inner and outer sides was calculated.

[0089] The stripped tubular cross-linked polyethylene insulation samples were placed in a ventilated thermal aging test chamber, and the working temperature was set to 135℃ for continuous accelerated thermal aging treatment for 168 hours. After the samples were removed, they were left to stand in a standard laboratory environment at 23℃ for 24 hours, and then a universal tensile testing machine was used to conduct a breaking test at a tensile rate of 250 mm / min. The elongation at break retention rate before and after the thermal aging treatment was calculated.

[0090] For the sample of Example 3 with built-in copper-plated constantan wire, a step-overload current was applied to its aluminum-based conductor using a high-current generator to induce rapid internal heating. A calibrated PT100 platinum resistance temperature sensor was tightly attached to the outer surface of the insulation layer as a reference control. The lead-out end of the constantan wire embedded inside the insulation layer was connected to a high-precision data acquisition instrument to continuously record and calculate the temperature converted from the micro-voltage signal of the thermocouple circuit. The error between the internal sensed temperature and the actual steady-state temperature inside the conductor was compared, and the response time from the application of current to the stable temperature indication was recorded.

[0091] Table 2: Test data records of insulation layer micro-crosslinking characteristics, aging retention rate and sensing performance

[0092] Experimental subjects outermost crosslinking degree (%) innermost crosslinking degree (%) Difference in crosslinking degree between inner and outer sides (%) 135℃ aging elongation retention rate (%) Steady-state error in temperature measurement (°C) Temperature measurement response time (s) Example 1 82.34 80.81 1.53 78.16 / / Example 2 81.76 80.52 1.24 77.92 / / Example 3 84.03 83.19 0.84 81.57 ±0.28 14.6 Comparative Example 4 80.12 68.85 11.27 53.84 / /

[0093] Note: / indicates that the cross-linked polyethylene insulation layer does not have an embedded copper-plated constantan wire intelligent sensing structure, making it impossible to test the temperature sensing performance.

[0094] in conclusion:

[0095] According to the data in Table 2, the degree of completion of the silane crosslinking reaction in the thickness direction is sensitive to the temperature gradient after extrusion. Comparative Example 4 uses a conventional 20℃ single-stage cooling water process, which generates a large temperature difference between the inner and outer sides of the insulation layer. The surface material cools down quickly, and the internal heat dissipation is hindered, resulting in a low degree of crosslinking in the inner layer material. The measured difference in crosslinking degree between the inner and outer sides is as high as 11.27%. This microscopic heterogeneity is prone to stress concentration under long-term thermo-oxidative aging. The macromolecular chain segments in the low crosslinking degree area break down during the internal stress release process, causing the elongation retention rate after aging at 135℃ to drop to 53.84%, which is far below the standard lower limit for the long-term safe operation of overhead insulated cables.

[0096] The segmented gradient cooling mechanism introduced in the examples slowed down the curing shrinkage rate of the outer resin. The incorporation of alumina improved the thermal conductivity within the matrix, reduced the thermal resistance of the thick-walled insulation layer, and allowed the crosslinking reactions of the inner and outer layers to proceed simultaneously. In Example 3, the difference in crosslinking degree between the inner and outer layers was compressed to 0.84%, and the micro-network of the entire insulation layer in the radial direction tended to be dense and uniform. The uniformly distributed crosslinking nodes dispersed local stress, enabling the insulation layer under this formulation to maintain an elongation retention of 81.57% even after severe thermal aging.

[0097] Conventional surface-mount sensing or infrared temperature measurement methods suffer from significant thermal conduction hysteresis errors. Example 3 involves directly embedding copper-plated constantan wire coated with a polyimide film deep within the extruded layer, constructing an in-situ thermocouple array without affecting the dielectric strength of the main insulation. Step current heating conditions verified that this built-in sensing circuit can reduce the thermal resistance of thick insulation materials, rapidly responding to conductor temperature changes within 14.6 seconds, with a steady-state temperature measurement error controlled within ±0.28℃. This provides reliable data for dynamic capacity expansion assessment and overheat warning of transmission lines.

[0098] Test Example 3: Macroscopic Interface Wetting Characteristics and Anti-icing Performance Test

[0099] Experimental description:

[0100] The outer layer sections of overhead cables prepared in Examples 1 to 3 and Comparative Example 5 were selected as experimental subjects, with Example 1 serving as a baseline control without an anti-icing functional layer. After cleaning and drying the sample surface with anhydrous ethanol, the interfacial wettability was tested using an optical contact angle meter at room temperature of 25°C. 5 μL of deionized water was dropped onto the sample surface using a microsyringe. After the droplet stabilized, the static water contact angle was recorded. Subsequently, the sample stage was slowly tilted until the droplet slipped, and the tilt angle at this point was recorded as the droplet roll-off angle.

[0101] A clean cable sample was fixed in a custom-made low-temperature test mold and placed in a -15℃ high and low temperature alternating damp heat test chamber. A cylindrical PTFE sleeve with an inner diameter of 10 mm was placed on the sample surface, and supercooled deionized water was injected to allow it to freeze in situ on the cable surface. The sample was left to freeze for 24 hours to allow the ice layer to fully bond with the interface. At the start of the test, the sleeve was removed, and a high-precision electronic push-pull force gauge was used to apply a shear force parallel to the cable axis to the side of the ice column at a constant rate of 1 mm / min. The peak load at the moment of macroscopic slippage of the ice column was recorded, and the ice adhesion strength was calculated by dividing it by the bonding bottom area.

[0102] Simulated de-icing tests were conducted using an artificial climate wind tunnel laboratory. A cable sample approximately 1.5m long was horizontally tensioned and installed within the wind tunnel test section. The ambient temperature was adjusted to -5℃, and a spray system was activated to simulate freezing rain conditions, causing an airfoil-shaped icing layer approximately 15mm thick to form on the windward side of the sample. After the icing process was completed, the wind speed was increased in increments of 0.5m / s, with each speed level maintained for 1 minute. The critical wind tunnel wind speed at which the icing layer completely peeled off or detached over a large area was recorded to evaluate the coating's natural de-icing performance under airflow excitation.

[0103] Table 3: Macroscopic interface wetting characteristics and de-icing test data records for each sample

[0104] Experimental subjects Static water contact angle (°) Droplet roll-off angle (°) Ice adhesion strength (kPa) Critical wind speed for ice shedding (m / s) Example 1 95.3 >90 (not scrolling) 138.6 12.4 Example 2 148.6 4.2 19.1 6.7 Example 3 151.2 3.5 15.8 6.2 Comparative Example 5 112.7 42.5 85.2 9.8

[0105] in conclusion:

[0106] According to the data in Table 3, the interfacial wetting properties affect the freezing process of supercooled water droplets on the contact surface. Figure 2 The graph illustrates the relationship between macroscopic surface wetting characteristics, ice adhesion strength, and de-icing wind speed distribution. The horizontal axis represents the static water contact angle of the sample surface measured at room temperature using the seated drop method, in degrees (°), ranging from 85 to 165. The vertical axis represents the ice adhesion strength between the icing layer and the cable interface, obtained by the shear method at -15°C, in kilopascals (kPa). Example 1, without any surface modification treatment, serves as a baseline control, exhibiting a static water contact angle of only 95.3°. The droplets spread over a large area on this surface, penetrating the pores of the polymer surface and freezing. A mechanical interlocking structure is formed at the solid-ice interface, resulting in a measured ice adhesion strength of 138.6 kPa. In a wind tunnel simulation, a wind speed of 12.4 m / s was required for the ice layer to peel off, posing a risk of overload and cable breakage in practical applications.

[0107] Comparative Example 5, containing only fluorinated resin, lacked the conditions for constructing micro / nano rough structures due to the absence of hydrophobic silica aerogel. Its measured contact angle was 112.7°, and the droplet exhibited significant hysteresis resistance (roll-off angle of 42.5°). In this case, the stress generated by the volume expansion during the freezing process of the supercooled water droplet could not be effectively released, and its ice adhesion strength was 85.2 kPa, insufficient to support passive self-cleaning under normal meteorological conditions.

[0108] Examples 2 and 3 utilize the pore network of fluorocarbon long chains and nanoscale silica aerogel to form a micro-nano hierarchical rough structure on the cable periphery. This composite layer can trap air, forcing a Cassie-Baxter transition at the solid-liquid interface. Example 3 achieves a superhydrophobic state with a static water contact angle of 151.2°, and water droplets can roll off at an angle of 3.5°. This non-wetting property reduces the actual contact area between ice crystals and the substrate, resulting in a significant decrease in interfacial adhesion, with the ice adhesion strength dropping to 15.8 kPa. Under the excitation of wind tunnel airflow, the extremely low interfacial adhesion force causes the ice layer to fracture under the aerodynamic pressure and gravity on the windward side, with macroscopic slippage occurring at a wind speed of only 6.2 m / s, demonstrating that this coating system can provide protection for the line in freezing weather.

Claims

1. A high-conductivity aluminum alloy core reinforced insulated overhead cable, characterized in that, The overhead cable comprises a high-conductivity aluminum alloy core, a stainless steel wire reinforcing layer wound around the outer periphery of the aluminum alloy core, and a cross-linked polyethylene insulation layer covering the outer surface of the stainless steel wire reinforcing layer. The high conductivity aluminum alloy core contains the following components by weight percentage: Fe 0.12-0.15wt%, Si 0.05-0.07wt%, Mg 0.02-0.03wt%, Zr 0.008-0.010wt%, with the balance being Al and unavoidable impurities; The stainless steel wire reinforcing layer is a prestressed network layer made of 316L stainless steel wire spirally twisted together. The stainless steel wire reinforcing layer has axial prestress cured inside and is tightly wrapped around the surface of the aluminum alloy core. The cross-linked polyethylene insulation layer is made from raw materials comprising the following parts by weight: 100 parts of polyethylene resin; Alumina 0.4–0.45 parts; 0.1–0.15 parts of hindered phenolic antioxidants; 1.5 to 2.5 parts of silane crosslinking agent; The difference between the outermost and innermost crosslinking degrees of the crosslinked polyethylene insulation layer in the thickness direction is ≤1.53%, wherein the outermost crosslinking degree is the crosslinking degree within 0.5 mm from the outer surface of the insulation layer, and the innermost crosslinking degree is the crosslinking degree of the insulation layer close to the surface of the stainless steel wire reinforcing layer.

2. The high conductivity aluminum alloy core reinforced insulated overhead cable according to claim 1, characterized in that, The weight percentage of the components in the high conductivity aluminum alloy core is as follows: Fe0.12wt%, Si0.05wt%, Mg0.02wt%, Zr0.0095wt%; Furthermore, the aluminum alloy core matrix contains dispersed Al3Zr nano-precipitates with a size of 10 nm.

3. The high conductivity aluminum alloy core reinforced insulated overhead cable according to claim 1, characterized in that, The axial prestress value in the stainless steel wire reinforcing layer is 346.8 to 400 MPa, and the grain size inside the 316L stainless steel wire is ≤2.5 μm.

4. The high conductivity aluminum alloy core reinforced insulated overhead cable according to claim 1, characterized in that, In the cross-linked polyethylene insulation layer raw material, the alumina has an average particle size of 20-40 nm and a specific surface area of ​​85-110 m2 / g; the hindered phenolic antioxidant is antioxidant 1010.

5. The high conductivity aluminum alloy core reinforced insulated overhead cable according to claim 1, characterized in that, Two copper-plated constantan wires are embedded parallel to each other along the axial direction inside the cross-linked polyethylene insulation layer. The outer surface of the copper-plated constantan wires is covered with a polyimide film with a thickness of 0.03 mm. The copper-plated constantan wires are spaced 2.5 mm apart, have a diameter of 0.18 mm, and have a temperature coefficient of resistance of ±5×10−6 / ℃.

6. The high conductivity aluminum alloy core reinforced insulated overhead cable according to claim 1, characterized in that, The outer surface of the cross-linked polyethylene insulation layer is also covered with an anti-icing functional layer. The thickness of the anti-icing functional layer is 0.15 to 0.18 mm, and it is formed by drying a mixed coating liquid containing fluorinated acrylate copolymer and hydrophobic silica aerogel.

7. A high conductivity aluminum alloy core reinforced insulated overhead cable according to claim 6, characterized in that, The mass ratio of the fluorinated acrylate copolymer to the hydrophobic silica aerogel in the mixed coating solution is 7:3; the fluorinated acrylate copolymer is a polymer compound containing trifluoroethyl side groups and having a glass transition temperature of -15℃; the hydrophobic silica aerogel has a porosity of ≥92% and a particle size of 50-100nm.

8. A high conductivity aluminum alloy core reinforced insulated overhead cable according to claim 1, characterized in that, The stainless steel wire reinforcing layer is formed by winding 316L stainless steel wire with a diameter of 0.8mm in a left-hand spiral twisting manner, with a pitch diameter ratio of 12 to 14 and a twisting tension of 120 to 150N.

9. A high conductivity aluminum alloy core reinforced insulated overhead cable according to claim 1, characterized in that, The axial prestress within the stainless steel wire reinforcing layer is formed by a composite segment of the stainless steel wire and the aluminum alloy core, which contains initial stranding tension, undergoing a low-temperature aging treatment at 180–190°C for 2 hours, followed by cooling to room temperature and solidification.

10. A high conductivity aluminum alloy core reinforced insulated overhead cable according to claim 1, characterized in that, The cross-linking degree distribution of the inner and outer sides of the cross-linked polyethylene insulation layer is formed by a segmented gradient cooling process after the raw material is extruded and coated at 195-200°C, and then subjected to water cooling at a temperature of 50°C and a cooling length of 1.2m, followed by air cooling at a temperature of 28°C and a cooling length of 0.8m.